Optimalisasi Pengawasan Keimigrasian Melalui Kebijakan Penggunaan Data Revervasi Penumpang di Tempat Pemeriksaan Imigrasi - Tony Yuri Rahmanto; Yuliana Primawardani (Sekolah Tinggi Ilmu Administrasi Nasional, 2023)
The policy of using passenger name records (PNR) at immigration checkpoints is one-way immigration authorities try to enforce the law and protect state security. This is done by exchanging passenger data in the Passenger Analyzing Unit (PAU) system owned by the Directorate General of Customs and Excise with immigration data in the Immigration Management Information System (SIMKIM) and dealing with suspected lawbreakers at the border. This paper uses a qualitative method and descriptive analysis to look at the policy of using PNR to control immigration as much as possible. The analysis results show that the proposed approach still needs help. For example, there are no rules about how the officers and workers of the Directorate General of Immigration and the Directorate General of Customs and Excise should do their jobs. Second, although the existing infrastructure does not meet established standards, it is still transportable. Thirdly, the data exchange collaboration agreement between the Directorate General of Immigration and the Directorate of Customs has not been formalized. Fourth, no authorized official or officer can manage and analyze PNR data. Therefore, the Director General of Immigration recommended overcoming various obstacles, including integrating the PNR system from Customs and Excises and Airline and Border Control Management (BCM).